2017
DOI: 10.1007/s11079-017-9437-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Spillover Effects of Unconventional Monetary and Exchange Rate Policies

Abstract: This paper explores the effects of unconventional monetary and exchange rate policies. We find that official foreign asset purchases have large effects on current accounts that diminish as capital mobility rises and spill over to financially integrated countries. There is an additional effect through the stock of central bank assets. Domestic asset purchases have an effect on current accounts only when capital mobility is low. We also find that rising US bond yields drive foreign yields, stock prices and depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
(2 reference statements)
0
28
0
1
Order By: Relevance
“…2 In these studies, the effects are normally considered under the assumption of the use of conventional tools of monetary policy (by the source country); although several recent studies look at the effects of unconventional tools of monetary stimulus that many central banks experimented with after the GFC. The US or the Euro area usually represent the source country due to their relatively influential position in the world economy (see, for example, Beckworth and Crowe 2013, Chen et al 2016, Edwards 2016, Potjagailo 2017, Gagnon et al 2017, Ma ckowiak 2007, Neely 2010, Rey 2016, Roger et al 2013, Punzi and Chantapacdepong 2017, Taylor 2013. Claus et al (2016) examine how shocks to US and Japanese monetary policy affect their own asset market and the spillover into each other's market for the period from January 1998 to June 2015.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…2 In these studies, the effects are normally considered under the assumption of the use of conventional tools of monetary policy (by the source country); although several recent studies look at the effects of unconventional tools of monetary stimulus that many central banks experimented with after the GFC. The US or the Euro area usually represent the source country due to their relatively influential position in the world economy (see, for example, Beckworth and Crowe 2013, Chen et al 2016, Edwards 2016, Potjagailo 2017, Gagnon et al 2017, Ma ckowiak 2007, Neely 2010, Rey 2016, Roger et al 2013, Punzi and Chantapacdepong 2017, Taylor 2013. Claus et al (2016) examine how shocks to US and Japanese monetary policy affect their own asset market and the spillover into each other's market for the period from January 1998 to June 2015.…”
Section: Previous Empirical Studiesmentioning
confidence: 99%
“…Importantly, our U.S. monetary policy surprises are much better identified because we use intraday data to compute changes in short-term U.S. Treasury yields in narrow windows bracketing FOMC announcements. Also related is a study by Gagnon et al (2017), who analyze the direct effects and cross-border spillovers of asset purchase programs and exchange rate policies employed by the major central banks in response to the global financial crisis. With regard to the unconventional policy measures employed by the Federal Reserve during this period, they find that policy-prompted increases in U.S. bond yields are associated with increases in local currency foreign bond yields and equity prices, as well as with a depreciation of foreign currencies.…”
Section: Related Literaturementioning
confidence: 99%
“…Furthermore, Miyakoshi et al (2017) showed that unconventional monetary practices implemented by the US, the Euro Area and Japan positively and significantly affected equity prices in developing Asian countries. Moreover, Gagnon et al (2017) provided evidence of higher equity quotes and lower currency values for foreign countries during periods of US extraordinary monetary policies. Fassas and Papadamou (2018) studied the risk-taking channel of monetary policy in the major European and U.S. equity markets.…”
Section: Literature Reviewmentioning
confidence: 99%